THE SOCIO-ECONOMIC TRANSFORMATION IN UKRAINE AS A PROSPECT OF CONVERGENCE WITH THE EUROPEAN UNION - Zvarych, Roman (Journal of European Economy, 2017)
For a country which takes transit geopolitical position between the West and the East, the participation in international integration processes is inevitable. In case with Ukraine, such participation will allow a country to ensure economic development and income growth. Membership in the European Union is a main step for transformation and stabilization of the Ukrainian economic development, income growth and life standard increase. Taking into account a substantial difference in the development of EU-15 and EU-10+2 (new EU members), which means income growth and convergence in the long term due to different approaches, for Ukraine it follows that an individual approach to socio-economic development should be taken. Membership in the European Union will be topical in the context of economic development and convergence with the economy of the European Community.